Internal Debt Issue And Sustainability Of Internal Debts: After 2000 Turkey Sample - Zafer Donmez (European Scientific Journal, ESJ, 2016)
Today, borrowing that has become a common problem of almost all countries has a great importance in the developing countries, for example Turkey, rather than developed countries. The reason is while internal debt is considered as provisional public revenue to balance the current economy in the developed countries, it is considered as consistent public revenue such as tax in the developing countries. From this view, internal debt that has increased over the years causes an accumulation called “snowball effect”. Public internal debt at high levels is negatively affected by macro economic factors such like manufacturing, investment, inflation, distribution of income. Uncontrollable increases of the internal debts make sustainability matter of debts a current issue. In the study, it has been analyzed if internal debts were sustainable in Turkey’s economy between the years of 2000 and 2014 by using the method of proportional analysis and it has been concluded that internal debts cannot be sustained especially in crisis periods.